A Rare Case of Thoracic Intradural Epidermoid Cyst after Spinal Cord Stimulator Insertion: A Case Report - Sun Ha Min, Ji Hae Lee, Jae Hyung Kim, Myeong Ja Jeong, Soung Hee Kim, Ji-Young Kim, Mi-jin Kang (대한영상의학회지, 2022)
Spinal epidermoid cysts are extremely rare benign tumors and can be congenital or acquired. Acquired spinal epidermoid cysts are found in the lumbosacral region. To our knowledge, no case of epidermoid cyst related to spinal cord stimulator insertion has yet been reported. We report the MRI findings of a rare case of thoracic intradural epidermoid cyst acquired after spinal cord stimulator insertion in a 50-year-old female.